Social tipping points and adaptation limits in the context of systemic risk: Concepts, models and governance - Juhola, Sirkku; Filatova, Tatiana; Hochrainer-Stigler, Stefan; Mechler, Reinhard; Scheffran, Jürgen; Schweizer, Pia-Johanna (Frontiers in Climate, 2022)
Physical tipping points have gained a lot of attention in global and climate change research to understand the conditions for system transition conditions when it comes to the atmosphere and the biosphere. Social tipping points have been framed as mechanisms in socio-ecological systems, where a small change in the underlying elements or behaviour of actors triggers a large non-linear response in the social system. With climate change becoming more acute, it is important to know whether and how societies can adapt. While social tipping points related to climate change have been associated with positive or negative outcomes, overstepping adaptation limits has been linked to adverse outcomes where actors' values and objectives are strongly compromised. Currently, the evidence base is limited, and most of the discussion on social tipping points in climate change adaptation and risk research is conceptual or anecdotal. This paper brings together three strands of literature - social tipping points, climate adaptation limits and systemic risks, which so far have been separate. Furthermore, we discuss methods and models used to illustrate the dynamics of social and adaptation tipping points in the context of cascading risks at different scales beyond adaptation limits. We end with suggesting further evidence is needed to identify tipping points in social systems, which is crucial for developing appropriate governance approaches.